Inisiasi Kampung Komplementer Untuk Optimalkan Kesehatan Ibu dan Anak - Ester Ratnaningsih; Lenna Maydianasari; Rahayu Widaryanti; Muflih Muflih (Lembaga Penelitian Dan Pengabdian Masyarakat Politeknik Kesehatan Muhammadiyah Makassar, 2021)
The majority of mothers who have toddlers in Karangrejo Sub-Village, Karangnongko, Tirtomartani Village, Kalasan Subdistrict come to the baby shaman to massage the baby and provide herbs to increase appetite in her child. The public also does not have knowledge of complementary therapies to address mild health complaints without chemical drugs such as cupping, accupoint and herbal therapy. The purpose of community service is to initiate the formation of complementary villages in Karangrejo Sub-Village . The activities carried out are complementary cadre training, baby healthy food movement, toddler and breastfeeding, healthy toddler movement and healthy living community movement with the use of herbs. Monitoring and evaluation are carried out with assistance to motivate the sustainability of the program. The result achieved is (1) The partner has formed and has a complementary village manager; (2) The partners have complementary cadres (3) The partners have carried out complementary village activities, namely healthy food movements for infants, toddlers and nursing mothers, monitoring growth and healthy community movements with the use of herbal plants